Interactive Media Development “Sing: Listen And Speak” Based on Acoustic Music For Language Introduction for Children Aged (5-6) Years in Kindergarten - Luthfi, Tasyfiah Aliya; Sumarni, Sri; Safitri, Erna Retna (Lembaga Bale Literasi, 2026)
Language learning in early childhood still faces obstacles in the form of limited interactive media that are appropriate to the characteristics of child development, especially in integrating auditory, visual, and linguistic aspects in an integrated manner. The use of existing digital songs tends to not pay attention to child-friendly musical elements and is not directed at strengthening thematic vocabulary. This study aims to develop an interactive media